2009
DOI: 10.1177/0363546509339364
|View full text |Cite
|
Sign up to set email alerts
|

Injury Patterns in Division I Collegiate Swimming

Abstract: Particular attention should be given to swimmers making the transition into collegiate level swimming. These data also suggest that injury surveillance and potential prevention strategies should focus on the shoulder for in-pool activities and the axial spine for cross-training activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 9 publications
8
95
1
7
Order By: Relevance
“…La prevalencia del dolor de hombro y el sexo no muestran relación, acorde con los resultados de otros estudios previos 13,18,21 . Sin embargo en la muestra de este estudio existe relación estadísticamente significativa (p=0,015) entre el IMC y la prevalencia del dolor de hombro, siendo más elevada entre los nadadores con mayor IMC.…”
Section: Dolor Con Relación a Factores Antropométricos Y Deportivosunclassified
See 2 more Smart Citations
“…La prevalencia del dolor de hombro y el sexo no muestran relación, acorde con los resultados de otros estudios previos 13,18,21 . Sin embargo en la muestra de este estudio existe relación estadísticamente significativa (p=0,015) entre el IMC y la prevalencia del dolor de hombro, siendo más elevada entre los nadadores con mayor IMC.…”
Section: Dolor Con Relación a Factores Antropométricos Y Deportivosunclassified
“…Estudios previos han obtenido resultados en la misma dirección 1,9,13,18 . Las variables de exposición al entrenamiento, relacionadas en algunos estudios transversales con el dolor de hombro 1,9,18 no muestran relación estadísticamente significativa en esta muestra, en la misma línea que otros estudios longitudinales (retrospectivos 21 y prospectivos 17 ), y transversales 12,13 . Se requieren estudios de mayor tamaño muestral en cada grupo de edad para poder analizar esta relación.…”
Section: Dolor Con Relación a Factores Antropométricos Y Deportivosunclassified
See 1 more Smart Citation
“…Thus, in this group, a large proportion of female athletes were injured, but male athletes incurred more injuries per athlete. In collegiate swimmers without disability, Wolf et al 19 found an injury prevalence of 72.7% in male and 70% in female athletes. Indeed, the pattern of injuries between men and women seems to shows few differences compared with the same sport among ablebodied athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the prevalence of pain was mainly in the shoulder (39.6%), thigh (22.6%), knee (20.8%), foot (1.9%) and ankle regions (1.9%) showing that the percentage of pain on the foot and ankle decreased as compared to the one in that time, probably due to technical improvement of the leg stroke during swimming styles. According to Wolf et al 16 , when assessing athletes in a university in the USA, 37% of these students were injured, and the part mostly reported was the shoulder (31%), followed by the neck (23.7%) and back (19.8%).…”
mentioning
confidence: 99%